Development of a SERS strategy to overcome the nanoparticle stabilisation effect in serum-containing samples: Application to the quantification of dopamine in the culture medium of PC-12 cells - Dumont, E.; De Bleye, C.; Cailletaud, J.; Sacre, P.-Y.; Van Lerberghe, P.-B.; Rogister, B.; Rance, G.A.; Aylott, J.W.; Hubert, Ph.; Ziemons, E. (Elsevier, 2018)
The analysis of serum samples by surface-enhanced Raman spectroscopy (SERS) has gained ground over the last years. However, the stabilisation of colloids by the proteins contained in these samples has restricted their use in common practice, unless antibodies or aptamers are used. Therefore, this work was dedicated to the development of a SERS methodology allowing the analysis of serum samples in a simple and easy-to-implement way. This approach was based on the pre-aggregation of the colloid with a salt solution. Gold nanoparticles (AuNPs) were used as the SERS substrate and, owing to its physiopathological importance, dopamine was chosen as a model to implement the SERS approach. The presence of this neurotransmitter could be determined in the concentration range 0.5 to 50 ppm (2.64 – 264 μM) in the culture medium of PC-12 cells, with a R2 of 0.9874, and even at lower concentrations (0.25 ppm, 1.32 μM) in another matrix containing fewer proteins. Moreover, the effect of calcium and potassium on the dopamine exocytosis from PC-12 cells was studied. Calcium was shown to have a predominant and dose-dependent effect. Finally, PC-12 cells were exposed to dexamethasone in order to increase their biosynthesis and release of dopamine. This increase was monitored with the developed SERS approach.